Efeito das impurezas ferro, alumínio e magnésio na cadeia de processamento químico do fosfato - Fernandes, Nilson José (2011)
The element phosphorus plays key role in plants metabolism. It is widely used as fertilizer. This element is usually found in insoluble forms (Ca10(PO4)6F2). The solubilization in phosphoric acid and/or superphosphates (SSP or TSP) processes are widely used in the fertilizer industry. Impurities (also called contaminants) contained in phosphates exert a significant influence on the processing of fertilizers as well as the quality of intermediates and final products. The objective of this work was to analyze the influence of some of these main impurities (iron, aluminum and magnesium) in the production chain TSPG fertilizer, which is the production of phosphoric acid, the acidulation of TSP and finally granulation of TSPG. Bench experiments were performed at each step. The contaminants concentrations from processing steps are interrelated in order to achieve a systemic analysis of the processing chain. The premises for the application of methodologies were playing the most typical parameters from industrial application. Igneous phosphate concentrate was used in the experiments. For contaminants concentrations variations were used magnetite (Fe2O3 source), the metal aluminum (Al2O3 source) and magnesium hydroxide (MgO source). Reductions in conversions, increases in viscosity and density of phosphoric acid were observed with increasing presence of these impurities. In the phosphogypsum filtration there was found an increase in resistivity of the cake with the increase of the impurities content. The iron mineral element promoted an increase in induction time of crystals nucleation. The increasing impurities concentration in the TSP acidulation caused reductions in P2O5 conversions (Neutral Ammonium Citrate soluble and Water Soluble), that caused the increased levels of residual phosphoric acid and free moisture in the TSP. An analysis of the specification for the TSP granulation in TSPG presented upper limit of impurities (MER) from phosphate concentrate around 0.15. The granulation of TSPG showed effects from the TSP, i.e., higher levels of residual phosphoric acid in the TSP assigned greater hardness, higher hygroscopicity and higher granulation factor to TSPG. The bench tests reproduced the current industrial setting.